In situ surface alkalinized g-C3N4 toward enhancement of photocatalytic H2 evolution under visible-light irradiation. Issue 8 (18th August 2015) - Li, Yunxiang; Xu, Hua; Ouyang, Shuxin; Lu, Da; Wang, Xin; Wang, Defa; Ye, Jinhua
Abstract : An in situ surface alkalization over g-C3 N4 achieves 14-fold enhancement in photocatalytic H2 evolution. Abstract : Surface-alkalinization over g-C3 N4 was realized by an in situ synthesis approach of introducing KCl and NH4 Cl during the polymerization of melamine. The characterization of the Fourier transform-infrared spectrum, X-ray photoelectron spectrum, and electron spin resonance spectrum over the sample synthesized in the presence of KCl/NH4 Cl and other reference samples indicated that the K ions played an essential role in breaking the periodic chemical structure of g-C3 N4 and meanwhile the trace amount of H2 O in melamine could supply OH ions to graft hydroxyl groups. The NH4 Cl mainly contributed to exfoliation of layered g-C3 N4 particles and pushing negative shift of the conduction-band level based on the measurements of the BET surface area and valence-band X-ray photoelectron spectrum. An optimal sample, g–C3 N4 –KCl/0.1 g NH4 Cl (CN–KCl/0.1 g NH4 Cl), achieved a more than 14-fold enhancement in photocatalytic H2 evolution under visible-light irradiation compared with the pristine g-C3 N4 . The enhanced photocatalytic efficiency could be attributed to the fact that the surface hydroxyl groups and the more negative conduction-band level can promote the separation of photocarriers and offer a stronger potential for water reduction, respectively.